MODULARITY: A MAJOR ASPECT TO MAINTAINABILITY (International Journal of Innovative Research in Computer Science & Technology, 2019)
Researchers and Practitioners advocated  that modularity aspect of software is highly desirable and  significant for developing quality oriented maintainable  software. Despite the fact modularity is vital and highly  significant aspect for software development process, it is  poorly managed. This paper here highlights the importance  of modularity broadly and also as an important contributor  of software maintainability. In this paper a correlation  between the major attributes of object oriented design and  modularity has been ascertained. A modularity  quantification model using multiple linear regression has  been proposed for object oriented design. Finally, the  validation of the proposed modularity quantification model  is made known by means of experimental tests and the  results show that the model is highly significant.
Keywords: Maintainability; Modularity; Reusability; Testability; Design phase; Object Oriented Design.